Effectiveness and safety of subcutaneous immunotherapy using a depigmented, polymerized extract of cat epithelium in allergic patients: a retrospective, real-world study - Jiménez-Blanco, María Aránzazu; González-Mendiola, María Rosario; Boteanu, Cosmin; Elera, Javier Dionicio; Sánchez-Millán, Maria Luisa; Ruíz-García, M.; Laguna, Jose Julio (Frontiers in Allergy, 2025)
BackgroundAllergy to animal epithelium is on the rise with an estimated 26% of European adults presenting to clinics for suspected inhalant allergy are sensitized to cats, and allergen avoidance measures are often difficult to implement and often ineffective.MethodsReal-world, retrospective study to evaluate the effectiveness and safety of subcutaneous immunotherapy (SCIT) with depigmented, polymerized cat epithelium extract (Dpg-pol-cat) in adult patients with moderate to severe allergic rhinitis/rhinoconjunctivitis with or without controlled asthma due to cat epithelium sensitization. The primary endpoint was to evaluate the effectiveness of SCIT with Dpg-pol-cat under real-life conditions, as measured by improvement in health-related quality of life (HRQoL) using the validated ESPRINT-15 questionnaire 24 months after treatment initiation.ResultsThe study included 28 patients. The median age was 35 years and the median duration of treatment with Dpg-pol-cat was 21.8 months. All patients had a 1-day rush build-up schedule. Significant and sustained improvements in all domains of the ESPRINT-15 questionnaire were observed from month 6 to month 24 of treatment, as well as in reduction of rescue medication use and better asthma control. Specific IgG4 levels increased significantly after 24 months of SCIT, although no significant change was observed in mean anti-Fel d 1 IgG4 levels. Most adverse reactions were local and mild, with systemic reactions, all grade <2 according to the 2010 World Allergy Organization grading system, occurring mainly during the build-up phase.ConclusionsSCIT with Dpg-pol-cat proved to be effective with an excellent safety profile in this real-world study, making it a good treatment option for patients with rhinitis/rhinoconjunctivitis and asthma due to allergy to cat epithelium.